1978
DOI: 10.1186/1297-9686-10-3-443
|View full text |Cite
|
Sign up to set email alerts
|

Analyse des liaisons entre la morphologie et l'aptitude au galop au trot et au saut d'obstacles chez le Cheval

Abstract: Alors que l'analyse discriminante permettait de distinguer facilement un trotteur d'un pur sang (5 p. ioo de déclassés) elle souligne la difficulté qu'il y a à distinguer un « Bon sauteur » d'un « Mauvais e (2 7 p. 100 de déclassés). Des tendances peuvent toutefois être dégagées de l'ensemble des calculs. Le sauteur est un cheval plutôt grand, très compact (large et près de terre), avec une croupe longue, large et fortement inclinée dont les angles des autres rayons moteurs (scapulum, humérus et fémur) sont fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The differences between elite and nonselected horses were small but significant for several variables, such as shoulder, pelvis and femur inclinations and shoulder, elbow, stifle and hock joints (Holmström 2001). The same type of weak significant relationships between conformation variables and jumping ability (in competitions) have been found (Langlois et al 1978). However, conformation measurements could be used as a descriptive tool to avoid a conformational weakness and to improve the likelihood of soundness.…”
Section: Conformation and Dressage Abilitysupporting
confidence: 57%
See 2 more Smart Citations
“…The differences between elite and nonselected horses were small but significant for several variables, such as shoulder, pelvis and femur inclinations and shoulder, elbow, stifle and hock joints (Holmström 2001). The same type of weak significant relationships between conformation variables and jumping ability (in competitions) have been found (Langlois et al 1978). However, conformation measurements could be used as a descriptive tool to avoid a conformational weakness and to improve the likelihood of soundness.…”
Section: Conformation and Dressage Abilitysupporting
confidence: 57%
“…Skeletal conformation measurements were made by image analysis. This method was adapted from a photogrametric method described previously by Langlois et al (1978). Seventeen anatomical markers were glued onto the skin to measure bone lengths and joint angles (Fig 1).…”
Section: Conformation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…For YHT data, the corresponding genetic correlations were low but with high s.e. Langlois et al (1978) and Holmströ m and Philipsson (1993) showed that differences in various measures of conformation had a limited impact on jumping performance.…”
Section: Genetic Analyses Of Young Horse Tests In Swedenmentioning
confidence: 99%
“…Kinematic analysis of showjumpers goes back to the early days of cinefilm (De Sévy 1918), but only recently more extensive analyses have been made of various types of jumps (Clayton and Barlow 1989;Clayton et al 1995;Colborne et al 1995). Here again, elite showjumpers have been studied (Clayton and Barlow 1991;Deuel and Park 1991;Clayton et al 1996) and relationships between conformation and performance have been sought (Langlois et al 1978). Recently, a large longitudinal study in showjumpers was concluded in which it was shown that the basic traits of jumping technique remained constant during development (Santamaría et al 2004) and that some prediction of future performance could be made based on foal jumping kinematics (Bobbert et al 2005).…”
mentioning
confidence: 99%